Scenes and Characteristics of Hindostan, Volume 2 With Sketches of Anglo-Indian Society - Roberts, Emma (Cambridge library collection. Travel and Exploration in Asia, 1835)
Emma Roberts' 1835 work, compiled from articles she published in the Asiatic Journal, was well received in India and England. Roberts lived in India from 1828 with her sister and her brother-in-law who served in the 61st Bengal infantry. In 1830 she moved to Calcutta, where she edited and wrote for the Oriental Observer and contributed to periodicals and annuals. Returning to London in 1832, she threw herself into the literary world, publishing in several different fields. This book reveals Roberts' sympathetic attitude to the Indian people and her genuine interest in providing a thorough and honest report of their culture. Volume 2 begins by describing Allahabad in northern India, and covers a wide variety of topics including diamonds, geology, climate, flora and fauna, superstition, litigation, children, tourism and sport. For more information on this author, see http://orlando.cambridge.org/public/svPeople?person_id=robeem